L-theanine intervention enhances human gamma delta T lymphocyte function - Bukowski, Jack F; Percival, Susan S (Nutrition reviews, 2008)
Human gamma delta T lymphocytes are a subset of T cells and are a first line of defense against microbes and tumors. These gamma delta T cells can be primed by nitrogen-containing bisphosphonates, and certain short-chain alkylamines. These primed gamma delta T cells have an enhanced capacity to proliferate and to secrete cytokines upon ex vivo exposure to a wide variety of microbes and tumor cells. The largest dietary source of alkylamines is L-theanine, an amino acid unique to tea beverages that is catabolized to ethylamine. Supplementation of subjects with capsules containing L-theanine and catechins has recently been shown to decrease the incidence of cold and flu symptoms, while enhancing gamma delta T cell function.